2006
DOI: 10.1039/b518059g
|View full text |Cite
|
Sign up to set email alerts
|

Very high concentrations of DDE and toxaphene residues in crocodiles from the Ord River, Western Australia: an investigation into possible endocrine disruption

Abstract: Organochlorine pesticide concentrations, particularly those of the DDT family and of toxaphene, were measured by gas chromatography in samples of liver and body fat taken from Australian freshwater crocodiles Crocodylus johnstoni at three locations along the Ord River in Western Australia. The three sampling sites were the irrigation area, downstream of the irrigation area, and well upstream of the irrigation area; the last site serving as the control. DDT and toxaphene were applied in large and known quantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…The very high DDE concentrations found in Australian crocodiles (Yoshikane et al, 2006) attest to the improbability of DDE being the cause.…”
Section: Relationship To Mortalities and Possible Other Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The very high DDE concentrations found in Australian crocodiles (Yoshikane et al, 2006) attest to the improbability of DDE being the cause.…”
Section: Relationship To Mortalities and Possible Other Effectsmentioning
confidence: 99%
“…(Woodword et al, 2011). Yoshikane et al (2006) reported a mean ∑DDT concentration of 252,000 ng/glm (max 671,000 ng/g lm) in Australian Freshwater Crocodile liver from the Ord River irrigation area, Australia (Table 3). They also reported that the crocodiles seemed healthy with normal blood parameters.…”
Section: Comparisons With Other Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, p,p'-DDE has been detected at very high concentrations even at the places where declines in the populations of wild animals are not currently observed (Yoshikane et al, 2006). Therefore, to confirm or disprove the reproductive toxicity of these two compounds the present study was undertaken and involved injecting the compounds into Japanese quail (Coturnix japonica) eggs.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although the use of DDT has declined, DDTr continue to be detected in environmental media and human tissues as they are persistent, lipophilic, and liable to bioaccumulation and biomagnication. [7][8][9][10][11] Even aer decades, the environmental risk of DDTr contaminated soil due to chemical factories has long been a signicant problem in most countries.…”
Section: Introductionmentioning
confidence: 99%